Harmful interference in regulatory perspective : legal rules for interference-free radio communication - Hofmann, Mahulena (Luxembourg legal studies, 2022)
This collection analyses the regulatory aspects of harmful interference faced by those entities operating space communication and broadcasting. While technology reacts to this international phenomenon with the development of continuously improving technological systems for preventing and combating harmful interference, its international regulatory and legal framework develops at a much slower pace. Issues discussed include the increasing deterioration of signals from broadcasting and communication satellites, including cases of intentional interference known as `jamming'; the human rights balance between freedom of expression and protection from hate speech; the efficacy of the current regulatory system and the legal consequences of non-compliance; the role of national authorities, and supranational bodies such as the EU and UN. The contributors include experts drawn from international and national academia, the ITU, national regulatory authorities and operators to present an international, multidimensional, and critical analysis of this complex phenomenon.